Numerical investigation on structure optimization and heat transfer of a phase change accumulator based on changing eccentricity and fin parameters - Yiting, Shi; Liting, Zhang; Yongwen, Yang; Tao, Zhang; Qifen, Li (Frontiers in Thermal Engineering, 2025)
In the contemporary era, the scarcity and strain of energy resources, combined with the pursuit of their efficient utilization, have posed critical challenges to the global community. Energy storage technology provides a solution to defer the utilization of heat or cold, thus tackling the root cause of energy shortages. Significantly, the integration of new energy sources has further enhanced the demand for energy storage. In contrast, the cost of heat storage is only one-tenth of that of electricity storage, which endows heat storage with more promising application prospects. Within the domain of heat storage, phase change heat storage has emerged as a prominent research focus due to its unique advantages such as high heat storage density, compact volume, and convenient control and matching capabilities. Consequently, we have made efforts to investigate the characteristics of phase change heat storage and improve heat transfer efficiency. Specifically, based on CFD simulation software and the enthalpy method mathematical model, a numerical model of the phase transformation process of tubular paraffin coupled with thermal conductivity and natural convection was established, and its heat absorption and heat release characteristics were simulated. The results indicate that the phase transition interface is symmetrical in general, but asymmetrical in the upper and lower parts, with the paraffin at the top having the fastest melting speed. To enhance the heat absorption and release process of phase change, the eccentric sleeve and fin were introduced. With the increase of eccentricity, the circulating flow range caused by natural convection expands. This is because the amount of paraffin in the lower part decreases and the thermal resistance reduces, which accelerates the melting speed. Moreover, increasing the eccentricity within a certain range is beneficial to accelerating the melting process. The addition of fins can significantly shorten the melting time of paraffin wax. Also, increasing the fin height and fin width can effectively reduce the melting time. However, as the fin height and fin width increase, the shortening gradient gradually decreases.